Patients Started on Hemodialysis with Tunneled Dialysis Catheter Have Similar Survival After Arteriovenous Fistula and Arteriovenous Graft Creation - Yuo, Theodore H. (J Vasc Surg, 2015)
OBJECTIVES: Current guidelines suggest that arteriovenous fistula (AVF) is associated with survival advantage over arteriovenous grafts (AVG). However, AVF often require months to become functional, increasing tunneled dialysis catheter (TDC) use, which can erode the benefit of AVF. We sought to compare survival in ESRD patients after creation of AVF or AVG in patients starting hemodialysis (HD) with TDC and identify patient populations that may benefit from preferential use of AVG over AVF. METHODS: Using U.S. Renal Data System (USRDS) databases, we identified incident HD patients in 2005 through 2008 and followed them through 2008. Initial access type and clinical variables including albumin levels were assessed using USRDS data collection forms. Attempts at AVF and AVG creation in patients who started HD through TDC were identified by CPT codes. We accounted for the effect of changes in access type by truncating follow-up when additional AVF or AVG were performed. Survival curves were then constructed, and log-rank tests used for pairwise survival comparisons, stratified by age. Multivariate analysis was performed with Cox proportional hazards regressions; variables were chosen using stepwise elimination. An interaction of access type and albumin level was detected, and Cox models using differing thresholds for albumin level were constructed. The primary outcome was survival. RESULTS: Among the 138,245 patients who started with TDC and had complete records amenable for analysis, 22.8% underwent AVF creation (Mean age±SD: 68.9±12.5 years, 27.8% mortality at 1 year) and 7.6% underwent AVG placement (70.2±12.0 years, 28.2% mortality) within 3 months of HD initiation; 69.6% remained with TDC (63.2±15.4 years, 33.8% mortality). In adjusted Cox proportional hazards regression, AVF creation is equivalent to AVG placement in terms of survival (HR 0.98, 95% CI 0.93–1.02; P=.349). AVG placement is superior to continued TDC use (HR 1.54, 95% CI 1.48–1.61; P<.001). In patients over age 80 with albumin levels greater than 4.0 g/dL, AVF creation is associated with higher mortality hazard compared to AVG creation (HR1.22, 95% CI 1.04–1.43, P=.013). CONCLUSIONS: For patients that start HD through TDC, placement of AVF and AVG are associated with similar mortality hazard. Further study is necessary in order to determine the ideal access for patients in whom the survival advantage of AVF over AVG is uncertain.